The Effect of Financial Literacy, Profit Sharing and Social Influence on Saving Interests : Case of Non-Muslim Customers at Islamic Bank in Bekasi - Supriyanto; Bayu Seno Pitoyo; Milda Handayani (East Asian Journal of Multidisciplinary Research, 2023)
This study was used to measure the effect of Financial Literacy, Profit Sharing and Social Influence on Saving Interests in Non-Muslim Customers at Islamic Bank Branch X Bekasi City. This research is a quantitative study in which the object used is the Non-Muslim Customers at Islamic Bank Branch X Bekasi City. The number of samples used in this study were 70 respondents. The design used in this research is hypothesis testing using the structural equitation model (SEM) – SmartPLS 3.0. The results of this study provide an explanation that the variables of finance literacy have a positive effect on saving interests in Non-Muslim Customers at Islamic Bank Branch X Bekasi City, Profit Sharing have a positive effect on saving interests in Non-Muslim Customers at Islamic Bank Branch X Bekasi City and Social Influence have thas no effect on saving interests in Non-Muslim Customers at Islamic Bank Branch X Bekasi City. This research has a limited object of research which is only carried out on the Non-Muslim Customers at Islamic Bank Branch X Bekasi City. This is used as a suggestion for future researchers. The novelty in this study combines the variables of Non-Muslim Customers at Islamic Bank Branch X Bekasi City.